Educational 2D Game On Civil Engineering For Civil Engineering Students - Teoh, Jing Hong; Bin Md. Fudzee, Mohd Farhan (Applied Information Technology And Computer Science, 2022)
While there were many construction games in the market, only a few addresses structural integrity in the game which is an important topic in civil engineering. Therefore, the project covers an Android, 2D educational, construction, budget management, puzzle game that will address the lack of similar structural engineering application. The title of the game is “Build for All”. This project will be developed based on gamification method which will be published on Android and evaluated with alpha/beta testing. SCRUM, a variant of Agile methodology was used during the development of the game. The requirements of end user or customer which is civil engineering students are researched and identified. Alpha and Beta Testing has been conducted with the latter having total of 18 testers in which 53.8% are target users. Based on their feedback, reviews are mostly positive with 83.4% are at least satisfied with the game in which coincides with the 38.9% or 7 people are interested at the gameplay. Therefore, the proposed game shall provide a rewarding, informative themed content that provide challenges and serve as a good reference or practice which structural engineering principles are an important aspect in the game.